2020
DOI: 10.1039/c9ee02543j
|View full text |Cite
|
Sign up to set email alerts
|

Revealing electrolyte oxidation via carbonate dehydrogenation on Ni-based oxides in Li-ion batteries by in situ Fourier transform infrared spectroscopy

Abstract: Carbonate oxidation via dehydrogenation on LiNi0.8Co0.1Mn0.1O2 at voltages as low as 3.8 VLi was revealed by in situ FT-IR measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
294
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(340 citation statements)
references
References 119 publications
23
294
0
Order By: Relevance
“…The CEI film is resulted from the decomposition of the carbonate solvent (Figure 9A2) and harmful for the cycling performance. [ 4a ] SR was supposed to happen between the LiPF 6 and moisture, as the F 1s spectra of all electrode materials split into two peaks, which is related to LiF/Li x PO y F z (≈685 eV) and C‐F (≈687 eV), respectively (Figure 9B1). [ 59 ] The reduced peak area of LiF and Li x PO y F z for the 3% LCO electrode demonstrates that the formation of the CEI in this sample is efficiently mitigated due to the construction of LCO on the surface (Figure 9B2), which is related to the conductive impedance of Li + passing through the CEI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CEI film is resulted from the decomposition of the carbonate solvent (Figure 9A2) and harmful for the cycling performance. [ 4a ] SR was supposed to happen between the LiPF 6 and moisture, as the F 1s spectra of all electrode materials split into two peaks, which is related to LiF/Li x PO y F z (≈685 eV) and C‐F (≈687 eV), respectively (Figure 9B1). [ 59 ] The reduced peak area of LiF and Li x PO y F z for the 3% LCO electrode demonstrates that the formation of the CEI in this sample is efficiently mitigated due to the construction of LCO on the surface (Figure 9B2), which is related to the conductive impedance of Li + passing through the CEI.…”
Section: Resultsmentioning
confidence: 99%
“…[ 3 ] Meanwhile, the highly reactive Ni 4+ produced at high voltage would induce parasitic side reactions (SR) at the interface of electrode/electrolyte, generating cathode electrolyte interphase (CEI) derived from the electrolyte decomposition, TM migration and dissolution. [ 4 ] The SR, coupled with the irreversible oxygen loss, further induces the capacity loss and voltage fading. [ 5 ] In this case, the biggest challenge is to improve the structure stability and stabilize the reversible oxygen‐related reactions, which are crucial to establish high energy density LIBs with superior cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…During charging, the voltage of the cathode electrodes is increased until a defined upper cut-off value leading to delithiated stage, i.e., extraction of Li ions from the layered structure [73,76,77].…”
Section: Micro Cracking Of Secondary Particle Structurementioning
confidence: 99%
“…Previous characterizations of the CEI suggest that its composition is nearly identical to that of the solid electrolyte interphase (SEI) on the anode side of the battery. For example, Fourier transform infrared (FTIR) spectroscopy (Aurbach et al, 1991;Kanamura et al, 1996;Aurbach, 1998;Hong et al, 2012;Zhang et al, 2020), mass spectrometry (MS) (Liu et al, 2016), and X-ray spectroscopies (Eriksson et al, 2002;Edström et al, 2004;Lu et al, 2009;Carroll et al, 2013;Malmgren et al, 2013;Yamamoto et al, 2014;Jarry et al, 2015;Fang et al, 2018;Källquist et al, 2019;Li et al, 2019) show that the CEI contains commonly observed electrolyte decomposition products such as PEO-type polymers, organic and inorganic carbonates, inorganic oxides, and fluorinated compounds. The similarity in composition between the CEI and the anodic SEI has led to the speculation that the CEI is formed from anode-cathode crosstalk (Cuisinier et al, 2013;Lu et al, 2013;Malmgren et al, 2013;Fang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%